Middle East Respiratory Syndrome Coronavirus Transmission in Extended Family, Saudi Arabia, 2014 - Arwady, M. Allison; Alraddadi, Basem; Basler, Colin; Azhar, Esam I.; Abuelzein, Eltayb; Sindy, Abdulfattah I.; Sadiq, Bakr M. Bin; Althaqafi, Abdulhakeem O.; Shabouni, Omaima; Banjar, Ayman; Haynes, Lia M.; Gerber, Susan I.; et al. (Emerging infectious diseases, 2016)
Risk factors for human-to-human transmission of Middle East respiratory syndrome coronavirus (MERS-CoV) are largely unknown. After MERS-CoV infections occurred in an extended family in Saudi Arabia in 2014, relatives were tested by using real-time reverse transcription PCR (rRT-PCR) and serologic methods. Among 79 relatives, 19 (24%) were MERS-CoV positive; 11 were hospitalized, and 2 died. Eleven (58%) tested positive by rRT-PCR; 8 (42%) tested negative by rRT-PCR but positive by serology. Compared with MERS-CoV-negative adult relatives, MERS-CoV-positive adult relatives were older and more likely to be male and to have chronic medical conditions. Risk factors for household transmission included sleeping in an index patient's room and touching respiratory secretions from an index patient. Casual contact and simple proximity were not associated with transmission. Serology was more sensitive than standard rRT-PCR for identifying infected relatives, highlighting the value of including serology in future investigations.